A General Hypoxia‐Responsive Molecular Container for Tumor‐Targeted Therapy - Zhang, Tian‐Xing; Zhang, Zhan‐Zhan; Yue, Yu‐Xin; Hu, Xin‐Yue; Huang, Fan; Shi, Linqi; Liu, Yang; Guo, Dong‐Sheng (Advanced materials (Weinheim), 2020)
Enhanced drug delivery can improve the therapeutic efficacy of drugs and help overcome side effects. However, many reported drug‐delivery systems are too complex and irreproducible for practical use. In this work, the design of a hypoxia‐responsive molecular container based on calixarene, called CAC4A, which presents a significant advance in practical, hypoxia‐targeted drug‐delivery, is reported. CAC4A enables a wide variety of clinical drugs to be quantitatively loaded to improve their solubility and stability, as well as enable the administration of reduced doses. Furthermore, as a result of its azo functional groups, which are sensitive to reduction within a hypoxic environment, it is possible to achieve tumor‐targeted drug‐release with reduced side effects. CAC4A fulfils all essential requirements for a drug‐delivery system in addition to multiple advantages, including facile preparation, well‐defined molecular weight, and structure, and universal applicability. Such features collectively enable supramolecular prodrugs to be formulated simply and reproducibly, with potential for bench‐to‐bedside translation. Moreover, CAC4A is amenable to other therapy modalities and can be facilely decorated with functional groups and hybridized with nanomaterials, providing ample possibilities for its role in future drug‐delivery systems. Carboxylated azocalix[4]arene is designed as a hypoxia‐responsive molecular container, which affords strong binding toward a series of chemotherapeutic drugs, and improves the drugs’ solubility and stability, demonstrating its universality as a supramolecular drug carrier. Taking one supramolecular prodrug as an example, the efficacy of this hypoxia‐targeted therapy is validated in vitro and in vivo.